AETIOLOGICAL CONSIDERATIONS OF ACQUIRED APLASTIC ANAEMIA - Malik, Saqib; Sarwar, Iram; Mehmood, Tariq; Naz, Farhat (Journal of Ayub Medical College Abbottabad, 2009)
Background: Acquired aplastic anaemia is one of the important causes of pancytopenia. This study was conducted to observe the mode of presentation of acquired aplastic anaemia and to find out its possible etiological factors. Methods: It is a hospital based descriptive study of 100 patients of acquired aplastic anaemia. Results: Out of 100 patients 60 were male and 40 female. Majority (44%) of the patients were between 12-20 years of age. Patient presented with variable symptoms majority (40%) with fever. Most of the patients had haemoglobin levels between 4-6 gm/dl. (53%). Seventy percent of the cases had no obvious cause, while in 30% some known causative factors were found. Chloramphenicol was found to be the most common causative drug. Mortality was 35%. Thirty patients were partially treated and 15 were lost to follow up. Twenty patients showed improvement with treatment. Conclusions: Acquired aplastic anaemia is common among males and more prevalent in younger age group. It is idiopathic in 70% cases while 30% had some cause. It has very high mortality. Doctors need to keep in mind this fatal condition in patients presenting with anaemia and should properly investigate before prescribing antibiotics and haematinics. Keywords: Aplstic anaemia pancytopenia, bone marrow suppression